Regulation of power generated from thermoelectric generators - Twaha, Ssennoga (2018)
In recent years, the efficiency of thermoelectric devices has improved greatly due thermoelectric material and device geometrical improvements. However, the efficiency of TEG is still low, being a subject of further research for more improvement. Hence, the main objective of the research carried out in this thesis is to analyse the performance of dc-dc converters with or without MPPT in conditioning the power generated from TEG. In light of this objective, the following case studies have been carried out.